2016
DOI: 10.2337/db15-1565
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Function of Hepatic FOG2 in Insulin Sensitivity and Lipid Metabolism Through PPARα

Abstract: Friend of GATA 2 (FOG2) is a transcriptional cofactor involved mostly in cardiac function. The aim of this study was to investigate the role of hepatic FOG2 in insulin sensitivity and lipid accumulation. FOG2 overexpression by adenovirus-expressing FOG2 (Ad-FOG2) significantly attenuates insulin signaling in hepatocytes in vitro. Opposite effects were observed when FOG2 was knocked down through adenovirus-expressing small hairpin RNA for FOG2 (Ad-shFOG2). Furthermore, FOG2 knockdown by Ad-shFOG2 ameliorated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In animal models, triggering inflammation has been shown to lead to a decrease in FOG2 expression in hepatocytes [ 30 ]. In another study, hepatic FOG2 was shown to attenuate insulin sensitivity by promoting glycogenolysis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, triggering inflammation has been shown to lead to a decrease in FOG2 expression in hepatocytes [ 30 ]. In another study, hepatic FOG2 was shown to attenuate insulin sensitivity by promoting glycogenolysis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical trials implicated that hypermethylated ZFPM2 protects against the occurrence and progression of metabolic complications in obesity and could affect immunity-related pathways ( 56 ). Meanwhile, some research implicated that decreasing ZFPM2 enhances insulin sensitivity via upregulating PPARA expression ( 57 , 58 ). Given that metabolic deterioration is the risk factor for both diseases, downregulating ZFPM2 should be the protective factor in psoriasis and AD, which contradicts our studies.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance is characterized by the accumulation of intrahepatic lipids due to an imbalance in lipid metabolism and free‐fatty acid oxidation . Meanwhile, adipose tissue is recognized as a key contributor to systemic insulin resistance .…”
Section: Mr and Diabetesmentioning
confidence: 99%